Abdominal Fat in Individuals with Overweight Reduced by Consumption of a 1975 Japanese Diet: A Randomized Controlled Trial. Issue 6 (15th April 2019) - Asano, Masaki; Kushida, Mamoru; Yamamoto, Kazushi; Tomata, Yasutake; Tsuji, Ichiro; Tsuduki, Tsuyoshi
Abstract : Objective: This study aimed to investigate whether the intake of the 1975 Japanese diet (JD) could reduce the amount of abdominal fat in people with overweight. Methods: Using a single‐blind randomized controlled trial, the modern diet (MD) was compared with the 1975‐type JD, which is based on the MD but includes five characteristics of the 1975 JD in an enhanced form. Overweight people were randomly assigned to an MD group ( n  = 30) and a JD group ( n  = 30). The participants consumed test diets that were provided three times a day for 28 days. Body composition measurements and blood biochemical examinations were performed before and after the test diet intake, and the proportions of change were compared. Results: Those in the JD group had significantly decreased BMI, fat mass, and levels of low‐density lipoprotein cholesterol, glycated hemoglobin, and C‐reactive protein ( P  = 0.002, 0.015, 0.014, 0.012, and 0.039, respectively) and significantly increased high‐density lipoprotein cholesterol levels compared with those in the MD group ( P  = 0.020). Conclusions: The intake of a diet with the characteristics of the 1975 JD may have beneficial effects on lipid metabolism in people with overweight and reduce the onset risk of metabolism‐related disorders, such as obesity and diabetes.